Cerebral Microbleeds in Patients With Acute Subarachnoid Hemorrhage. Issue 2 (30th October 2013) - Jeon, Sang-Beom; Parikh, Gunjan; Choi, H.Alex; Badjatia, Neeraj; Lee, Kiwon; Schmidt, J.Michael; Lantigua, Hector; Connolly, E.Sander; Mayer, Stephan A.; Claassen, Jan
Abstract: BACKGROUND: Cerebral microbleeds (CMBs) are commonly found after stroke but have not previously been studied in patients with subarachnoid hemorrhage (SAH). OBJECTIVE: To study the prevalence, radiographic patterns, predictors, and impact on outcome of CMBs in patients with SAH. METHODS: We analyzed retrospectively 39 consecutive patients who underwent T2*-weighted gradient-echo imaging within 7 days after onset of spontaneous SAH. We report the frequency and location of CMBs and show their association with demographics, vascular risk factors, the Hunt-Hess grade, the modified Fisher Scale, the Acute Physiological and Chronic Health Evaluation II, magnetic resonance imaging findings including diffusion-weighted imaging lesions, and laboratory data, as well as data on rebleeding, global cerebral edema, delayed cerebral ischemia, seizures, the Telephone Interview for Cognitive Status, and the modified Rankin Scale. RESULTS: Eighteen patients (46%) had CMBs. Of these patients, 9 had multiple CMBs, and overall a total of 50 CMBs were identified. The most common locations of CMBs were lobar (n = 23), followed by deep (n = 15) and infratentorial (n = 12). After adjustment for age and history of hypertension, CMBs were related to the presence of diffusion-weighted imaging lesions (odds ratio, 5.24; 95% confidence interval, 1.14–24.00; P = .03). Three months after SAH, patients with CMBs had nonsignificantly higher modified Rankin Scale scores (odds ratio, 2.50; 95% confidence interval, 0.67–9.39; P = .18). CONCLUSION: This study suggests that CMBs are commonly observed and associated with diffusion-weighted imaging lesions in patients with SAH. Our findings may represent a new mechanism of tissue injury in SAH. Further studies are needed to investigate the clinical implications of CMBs.